Comparative Analysis of Green Accounting, Intellectual Capital and Leverage on Profitability (Empirical study on mining sector companies listed on the Indonesia and Malaysia Stock Exchanges 2018-2023) - Meidirahma, Azzahra; Indriawati, Fitri (Baca Dulu Publisher, 2025)
This research aims to see and analyze the comparison of green accounting, intellectual capital and leverage on profitability. The population in this research is all mining companies listed on the Indonesia and Malaysia Stock Exchanges for the 2018-2023 period. The sampling technique in this research is a purposive sampling technique by determining several sampling criteria, so that 120 Indonesian companies and 102 Malaysian companies were used as samples in this research. The data analysis technique used in this research is Multiple Linear Regression with the help of SPSS Version 26. The results of this research are that there are differences in profitability, green accounting, intellectual capital in Indonesia and Malaysia. Meanwhile, there is no difference in leverage in Indonesia and Malaysia. Then Green Accounting and Intellectual Capital have a positive influence on profitability. Meanwhile, Leverage has no effect on profitability.